Hello, Mallory - Martin, Ann M., 1955- (New York : Scholastic, 1988)
Eleven-year-old Mallory is excited when it looks like she may be invited to join the Baby-sitters Club, but the baby-sitters have to learn some lessons in fairness first.
"An Apple paperback.".
4.8
3-6
Keywords: Babysitters -- Fiction; Clubs -- Fiction; Race relations -- Fiction; Babysitters -- Fiction; Clubs -- Fiction; Race relations -- Fiction